2014
DOI: 10.1177/230949901402200210
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty through the Mini-Incision (Micro-Hip) Approach versus the Standard Transgluteal (Bauer) Approach: A Prospective, Randomised Study

Abstract: Purpose. To compare outcome after total hip arthroplasty (THA) through the mini-incision approach versus the standard transgluteal approach. Methods. 80 women and 63 men aged 33 to 89 (mean, 62) years with primary osteoarthritis of the hip were randomised to undergo unilateral THA through a mini-incision approach (Micro-hip, n=55) or standard, lateral, transgluteal approach (Bauer, n=88). Levels of haemoglobin, haematocrit, serum creatine kinase, and C-reactive protein, length of hospital stay, mobilisation, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…A total of 2925 studies were excluded due to not matching the selection criteria. In the end, nine studies were included in the review [ 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2925 studies were excluded due to not matching the selection criteria. In the end, nine studies were included in the review [ 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine randomized controlled trials (RCTs) were analyzed in this systematic review [ 8 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Four of them compared DAA to the standard lateral approach (LA) [ 8 , 21 , 22 , 27 ], three of them compared DAA to the standard posterior approach (PA) [ 19 , 24 , 28 ], and two compared DAA to the posterolateral approach (PLA) [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, MISLA approach was associated with shorter operating time, less blood loss and better functional results (HHS and WOMAC score) on the day of discharge, 6 weeks and 3 months postoperatively [53]. In 2014 Dienstknecht et al (2014) compared muscle damage between conventional lateral, transgluteal approach (Bauer) (LA) and mini-incision (MIS-LA) approach with CRP and CK markers. Serum markers were measured at 2 nd and 7 th POD.…”
Section: Lateral Approach Versus Minimally Invasive Lateral Approachmentioning
confidence: 99%
“…As previously mentioned, the posterior approach is associated with a risk of dislocation but this finding has not been compared specifically to the direct lateral approach 6 . Pain assessments, although a subjective measure, have also indicated that patients who undergo THA through a lateral approach experience more discomfort than those undergoing a DAA 43,44 , narcotic analgesic use was also reported to be increased in patients who underwent PA compared with the DAA 45 . There does not appear to be a significant difference between the PA and direct lateral approaches peri-operatively, however pain levels during recovery for both are slightly elevated compared to the DAA which is likely due to the relatively muscle-sparing approach of this latter technique.…”
Section: Perioperative Outcomesmentioning
confidence: 99%